Penerapan Model Pembelajaran Kooperatif Tipe Talking Chips Dipadukan Jeopardy Games untuk Meningkatkan Keterampilan Kerja sama dan Hasil Belajar Siswa pada Materi Ekologi Kelas X MIPA SMA Negeri 7 Surakarta - Dahlia, Resita Sekar; Maridi, Maridi; Sari, Dewi Puspita (Universitas Sebelas Maret, 2019)
This study aims to improve and describe the increase in cooperative competence and student learning outcomes in the ecology material in class X MIPA SMA Negeri 7 in Surakarta through the application of the Talking Chips type cooperative learning model combined with Jeopardy Games. This research is a classroom action research). The research was conducted in two cycles. The subjects of this study were students of class X MIPA 5 SMA Negeri 7 in Surakarta consisting of 36 students. The technique of collecting data is done through observation observation sheets, evaluation questions, interviews, and documentation. The results showed that the application of the Talking Chips learning model combined with Jeopardy Games could improve the cooperation skills and student learning outcomes from pre-cycle to cycle I and from cycle I to cycle II. The average number of cooperative skills averages 41.2%; 57.41%; and 84.3%. The average achievement of combined cognitive contributions is 61.11; 74,92; and 83.92. The average achievement of affective contributions was 38.19%; 60.1%; and 88.19%. The average achievement of the combined psychomotor aspects is 33.33%; 56.6%; and 85.07%. The conclusion of this study is the application of the cooperative learning model of Talking Chips type combined with Jeopardy Games to improve cooperation skills and student learning outcomes in the ecology material of class X MIPA SMA Negeri 7 in Surakarta